Perbandingan Sistem Administrasi Negara Indonesia Dengan Brunei Darussalam - Aizah Dien Putri Ambarizki (Institut Riset dan Pengembangan Indonesia, 2024)
The state is a place where people can live their lives well and maintain social peace. Indonesia and Brunei Darussalam have their own characteristics and systems in running the wheels of life, of course there are differences in terms of social, economic and political aspects. This research aims to compare and describe the state administration system of Indonesia and Brunei Darussalam. The research was conducted using a qualitative method that is a library study (library research). Data sources come from journal articles, literature, online mass media, and the Internet. The data collection technique in this research is documentation, through written relics mainly in the form of archives and including books on opinions, theories, arguments, concepts, or laws related to research problems. The results showed that there are differences and similarities between the Indonesian and Brunei Darussalam state administration systems, starting from the Indonesian form of government in the form of a Republic while Brunei Darussalam is in the form of an Absolute Monarchy. The head of state of Indonesia is the president while Brunei Darussalam is the Sultan. In the country's profile which includes geographical location, demographics, economy, and accounting, then the government system, and bureaucracy there are also differences. The comparison is expected to be useful for the development of concepts and theories of the State Administration System.